#### Question

Solve the following pair of linear equations.

(a − b) x + (a + b) y = a^{2}− 2ab − b^{2}

(a + b) (x + y) = a^{2} + b^{2}

clickto share

#### Solution

You need to to view the solution

Is there an error in this question or solution?

#### Related Questions VIEW ALL [5]

#### Reference Material

Solution for question: Solve the following pair of linear equations. (a − b) x + (a + b) y = a2− 2ab − b2, (a + b) (x + y) = a2 + b2 concept: Equations Reducible to a Pair of Linear Equations in Two Variables. For the course CBSE